The Global South political economy of health financing and spending landscape – history and presence. (16th November 2021) - Jakovljevic, Mihajlo; Liu, Yansui; Cerda, Arcadio; Simonyan, Marta; Correia, Tiago; Mariita, Richard M.; Kumara, Ajantha Sisira; Garcia, Leidy; Krstic, Kristijan; Osabohien, Romanus; Toan, Tran Khanh; Adhikari, Chiranjivi; et al.
Abstract: The Global South nations and their statehoods have presented a driving force of economic and social development through most of the written history of humankind. China and India have been traditionally accounted as the economic powerhouses of the past. In recent decades, we have witnessed reestablishment of the traditional world economic structure as per Agnus Maddison Project data. These profound changes have led to accelerated real GDP growth across many LMICs and emerging countries of the Global South. This evolution had a profound impact on an evolving health financing landscape. This review revealed hidden patterns and explained the driving forces behind the political economy of health spending in these vast world regions. The medical device and pharmaceutical industry play a crucial role in addressing the unmet medical needs of rising middle class citizens across Asia, Latin America, and Africa. Domestic manufacturing has only been partially meeting this ever rising demand for medical services and medicines. The rest was complemented by the participation of multinational pharmaceutical industry, whose focus on investment into East Asia and ASEAN nations remains part of long-term market access strategies. Understanding of the past remains essential for the development of successful health strategies for the present. Political economy has been driving the evolution of health financing landscape since the establishment of early modern health systems in these countries. Fiscal gaps these governments face in diverse ways might be partially overcome with the spreading of cost-effectiveness based decision-making and health technology assessment capacities. The considerable remaining challenges ranging from insufficient reimbursement rates, large out-of-pocket spending, and lengthy lag in the introduction of cutting-edge technologies such as monoclonal antibodies, biosimilars, or targeted oncology agents, might be partially resolved only in the long run.